2009
DOI: 10.1243/14644207jmda268
|View full text |Cite
|
Sign up to set email alerts
|

A nanometre-scale fibre-to-matrix interface characterization of an ultrasonically consolidated metal matrix composite

Abstract: • This is an article from the journal, Proceedings of the IMechE, Part L:Journal DOI: 10.1243/14644207JMDA268Abstract: Future 'smart' structures have the potential to revolutionize many engineering applications. One of the possible methods for creating smart structures is through the use of shape memory alloy (SMA) fibres embedded into metal matrices. Ultrasonic consolidation (UC) allows the embedding of SMAs into metal matrices while retaining the SMA's intrinsic recoverable deformation property. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…80 mm by 25 mm) and then coating it with a layer of self-adhesive polyimide tape (75 μm thick Kapton™ tape). This aluminium substrate is commonly used with UAM [6][7][8]26] and the polyimide tape has excellent insulating, mechanical and thermal properties. The polyimide tape also provides an excellent surface for the dispensing of the conductive materials and past research has shown that it can withstand the mechanical loads introduced during UAM [10].…”
Section: Sample Preparation and Syringe Dispensingmentioning
confidence: 99%
See 1 more Smart Citation
“…80 mm by 25 mm) and then coating it with a layer of self-adhesive polyimide tape (75 μm thick Kapton™ tape). This aluminium substrate is commonly used with UAM [6][7][8]26] and the polyimide tape has excellent insulating, mechanical and thermal properties. The polyimide tape also provides an excellent surface for the dispensing of the conductive materials and past research has shown that it can withstand the mechanical loads introduced during UAM [10].…”
Section: Sample Preparation and Syringe Dispensingmentioning
confidence: 99%
“…This allowed researchers in the past to create composite metal matrix structures with embedded functional materials and other smart features, such as optical fibres [5,6], shape memory alloy fibres [7,8], other shape memory and magnetostrictive materials for embedded sensing applications [9] and smart switches for a structural antenna [10].…”
mentioning
confidence: 99%
“…The most applicable method based on prior literature is Focussed Ion Beam (FIB) milling in combination with Dual SEM imaging in order to analyse and assess the grain structure of the processed materials (Friel and Harris, 2010). This was performed through the use of a Nova 600 Nanolab Dual Beam Focused Ion Beam -Scanning Electron Microscope (FEI, Oregan, USA).…”
Section: Surface Grain Refinementmentioning
confidence: 99%
“…A second unique feature of UAM that makes it highly suitable for manufacturing MMCs is the large degree of localized plastic flow observed in the interlaminar region during foil deposition. This plastic flow allows for sound mechanical encapsulation of components by the matrix material [11]. To date, this ability has been utilized to incorporate a variety of fibers such as Silicon Carbide (SiC) for localized stiffening, Shape Memory Alloy (SMA) http for actuation and optical fibers for sensing [12][13][14].…”
Section: Introductionmentioning
confidence: 99%